Yummy Cafe Sdn. Bhd. / Nurhaidah Hanim Jamaludin - Jamaludin, Nurhaidah Hanim (2020)
Yummy Cafe Sdn. Bhd. is a cafe that provide only one special menu of bread which is Japanese Milk Bread and one menu of coffee which is Caramel coffee. The production of this bread and coffee is using premium ingredients and made with special recipe from Japan. Yummy Cafe’s first branch is located at Pasir Gudang, Johor. This place is a strategic place because it is near with public transport, residential area offices, and school. So that, it will be the main in the area and there also will be available for food delivery for example food panda. So, the customers can easily get the order from home through the food delivery. The price for the Japanese Milk Bread is RM20 and the for Caramel Coffee is RM15. It is affordable and suitable for all people to consume either kids until old citizen. The customer will get coupon for every fifth purchases in our cafe. Other than that, there are discount will be given when special event coming such as Eid Aidilfitri or Chinese New Year. We promote our business by media social including Facebook, Instagram and and Whatsapp so that, Yummy Cafe will be viral and trending in Malaysia. If the customer wants to reach us, they can directly call us or massage in Instagram or Facebook.